Case report: Granulomatosis with polyangiitis patient presented with a mass in the aortic root - Teng, Yinyan; Chen, Mei; Chen, Zhongwei; Zhang, Xiaowei; Li, Zhongyun; Liao, Shusheng (Frontiers in Immunology, 2024)
Granulomatosis with polyangiitis (GPA) is an autoimmune inflammatory disease that affects small- and medium-sized blood vessels in the body, representing a rare entity. Cardiac involvement was identified as an independent risk factor for death in GPA patients, yet it has not been systematically elucidated in previous literature. Cardiac lesions in patients with GPA can manifest in various ways, such as pericarditis, myocarditis, coronary vasculitis, valvular abnormalities, conduction system abnormalities, and heart failure. Herein, we report a 55-year-old woman with GPA; she had a 2-year history of recurrent episodes of headache, accompanying sickness, and fatigue, which have been aggravated for the past half-month. The main manifestation is presenting as a mass in the aortic root, which was successfully diagnosed by multimodality imaging (including two-dimensional echocardiography, contrast-enhanced ultrasound, and computed tomography). After treatment with methylprednisolone and cyclophosphamide, the patient’s symptoms significantly improved and she remained asymptomatic over 6 months of follow-up. This article will enrich our knowledge about cardiac involvement in GPA patients and highlights the value of imaging, especially ultrasound, in the diagnosis and post-treatment follow-up of this condition.